Production, crystallization and X-ray diffraction analysis of two nanobodies against the Duffy binding-like (DBL) domain DBL6∊-FCR3 of the Plasmodium falciparum VAR2CSA protein - Vuchelen, Anneleen (International Union of Crystallography, 2013)
The VAR2CSA protein has been closely associated with pregnancy-associated malaria and is recognized as the main adhesin exposed on the surface of Plasmodium falciparum-infected erythrocytes. Chondroitin sulfate A was identified as the main host receptor in the placenta. Single-domain heavy-chain camelid antibodies, more commonly called nanobodies, were selected and produced against the DBL6∊-FCR3 domain of VAR2CSA. Crystals of two specific nanobodies, Nb2907 and Nb2919, identified as strong binders to DBL6∊-FCR3 and the full-length VAR2CSA exposed on the surface of FCR3 P. falciparum-infected erythrocytes, were obtained. Crystals of Nb2907 diffract to 2.45 Å resolution and belong to space group C2 with unit-cell parameters a = 136.1, b = 78.5, c = 103.4 Å, β = 118.8°, whereas Nb2919 crystals diffract to 2.15 Å resolution and belong to space group P4(3)2(1)2 with unit-cell parameters a = b = 62.7, c = 167.2 Å.